A numerical investigation on the hybrid spur gears: Stress and dynamic analysis. (January 2022) - Yılmaz, Tufan G; Doğan, Oğuz; Karpat, Fatih
In this study, the effect of rim thickness of hybrid gears on the root stress, joint stress, tooth stiffness, natural frequency, and dynamic behavior are examined numerically. Hybrid gears consist of two materials, which are steel for the teeth-rim and hub regions of gear, carbon fiber reinforced plastic (CFRP) for the web region. Adhesive bonding is assumed for the joining of steel and composite materials. FE method is used to evaluate tooth root stress, joint stress, tooth deformation, and the natural frequency of hybrid gears. The adhesive is defined by cohesive zone modeling (CZM). Moreover, 2-DOF dynamic analyses are implemented to obtain dynamic factors and static transmission error. According to results, hybrid gears have substantial potential to reduce the mass of gear transmission systems with no adverse effect on root stress and dynamic factor if the design parameters are appropriately selected. Besides, rim thickness is found as a critical parameter for the hybrid gears since when its value changes from 0.5xm to 3xm, the root stress decreases 10% while the tooth stiffness and torque capacity increase 20% and 65%, respectively.